(3YWQ GdYQhSs - (3CHj GdeMGSf eMeO Hf YHO GdhgGH Hf TYHGf Hf OGhhO GdgePGfj GdcGXej,J (B1303 (3g` s
(3ChdgG (B:s
(3jLH MeO hGLH LYd eYTQ GdHTQ ef Gdeecf ecef GdfaS GdfGWbI s
(3BNQgG (B:s
(3abd hGSJYf HGdaQO oHTQi HdjdmI dgG CQNhG TeS GdSeG bGHdJ HOQG aGdMeO ddg GdPj ef YdjfG HEJeGeg hEceGdg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B258 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B268s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B40 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdCOHs